Evaluation of the drying methods and conditions with respect to drying kinetics, colour quality and specific energy consumption of thin layer pumpkins - Ismail, O.; Kocabay, O. G. (BULGARIAN ACAD SCIENCE, 2016)
In this study, the effects of dry air temperature and power levels when drying pumpkin (Cucurbita pepo L.) slices by five different methods was investigated experimentally. Pumpkin slices were dehydrated by five different drying methods: open-sun, vacuum, microwave, infrared and hot air drying. In particular, the experiments were carried out at two different microwave power levels (90 and 180 W), infrared power levels (83 and 125 W) and hot air temperatures (50 and 70 degrees C) to investigate the effects of these factors on the microwave, infrared and hot-air drying, respectively. The vacuum drying experiment was carried out in one vacuum oven dryer at a constant temperature of 50 degrees C and a pressure of 0.1 kPa. The experimental moisture data was fitted to some models (namely Lewis, Henderson and Pabis, Page, Logarithmic, Aghbashlo et al., Verma et al. and Midilli et al. models) available in the literature and according to the results, the Midilli et al. model is superior to the others in explaining the drying behavior of pumpkin slices. The energy efficiency and diffusion coefficients increased with the increase in microwave power. In terms of colour criteria the best. values were obtained by the hot-air and open-sun drying methods.
Keywords: colour; drying models; mathematical models; MICROWAVE; AIR; PRETREATMENTS; PARAMETERS; VACUUM; SLICES; CARROT; FRUITS; MODEL; Chemistry